A comparison study of flow analysis in 2-plate mould and 3-plate mould using computer software analysis - M.A, Amran; A.R. , Samsudin; R.H., Hambali (2007)
This paper studies the comparison of flow analysis in 2-plate mould and 3-plate mould on an Electronic Cash Register (ECR) plastic product using computer software analysis. There are three parts in ECR plastic product which including top casing, bottom casing and paper holder. Improvements on design of gate, runner, sprue, water holes and plastic parts were made to ensure optimum result analysis. This project started from design all the three parts of 3D modeling in the Unigraphic software and then transfer to Rhinoceros software for post processing and finally used Moldex software as a final stage for flow analysis in 2-plate and 3-plate mould. In the Moldex software the filling melt front time, packing melt front time, cooling and warpage analysis were done to determine and to solve the part defects which including short shot, unequal filling, over filling, welding line, cooling time and measured the value of warpage. Some calculations were done to determine the size of gate, runner and sprue to ensure the smooth flow of plastic material into the cavities area. In addition, calculations had been used for water holes design, which based from the distance of plastic parts surface to the distance of external diameters of water holes. This project showed encouraging on analysis results for all the three parts of ECR product. It solved various problems including short shot, unequal filling, overfilling, welding line, cooling time and measured the warpage value on the all three parts.